2019
DOI: 10.1097/tp.0000000000002882
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin Improves the Quality and Function of Hypothermic Preserved Islets by Its Antioxidative and Anti-inflammatory Effect

Abstract: Background. Islet transplantation is a promising option for the treatment of type 1 diabetes. However, the current lack of practical techniques for the isolated islets preservation still hampers the advancement of life-saving islet transplantation. Islet suffers from internal or external stimuli-induced oxidative stress and subsequent inflammation during preservation, which leads to disappointing outcomes regarding islet yield, survival, and function. Reactive oxygen species (ROS) overproduction is the primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 35 publications
5
35
0
Order By: Relevance
“…Many studies have reported a negative association between BIL levels and a range of diseases associated with oxidative stress, such as diabetes (27), asthma (28), and inflammatory bowel disease (29). Yao et al found that short-term preservation of BIL could prevent cell damage and maintain the viability and function of transplanted islets (30). The results of the present study also revealed lower BIL levels in the BPPV group with statistical differences between males and females.…”
Section: Bil and Bppvsupporting
confidence: 68%
“…Many studies have reported a negative association between BIL levels and a range of diseases associated with oxidative stress, such as diabetes (27), asthma (28), and inflammatory bowel disease (29). Yao et al found that short-term preservation of BIL could prevent cell damage and maintain the viability and function of transplanted islets (30). The results of the present study also revealed lower BIL levels in the BPPV group with statistical differences between males and females.…”
Section: Bil and Bppvsupporting
confidence: 68%
“…Biliverdin, as one main component in the BVSF hydrogel system, also contributed to the wound repair. Our previous research indicated that bilirubin possesses a power anti-inflammatory property, which showed significant cytoprotective effects against oxidative and inflammatory damage in multiple cell lines 40 , 63 - 65 . Biliverdin, as a precursor substance of bilirubin, has also been demonstrated as an important cytoprotective and anti-inflammatory molecule 34 , 35 .…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, a large number of active drugs have emerged to improve therapy for acute pancreatitis by inhibiting the NF-κB signaling pathway in experiments (Cen et al., 2016 ; Tao et al., 2019 ). Bilirubin is a bioproduct, and possessed potent antioxidant and anti-inflammatory properties (Yao, Jiang, et al., 2019 ; Yao, Jiang, 2019 ; Yao, Huang, 2020 ; Yao, Sun, 2020 ). Our previous study also indicated that bilirubin could inhibit the NF-κB mediated pro-inflammatory signaling pathway, and significant reduced the progression of acute pancreatitis in a rat model (Wang et al., 2016 ).…”
Section: Molecular and Cellular Mechanisms Of Acute Pancreatitismentioning
confidence: 99%
“…Nanotechnology has gained considerable attention as a drug delivery carrier (Kou et al., 2013 , 2017a , 2017b , 2018a , 2018b , 2018c ). One of the most well-known benefits of nanomedicine is their selective accumulation by the enhanced permeability and retention (EPR) effect at tumor sites (Yao et al., 2018 ; Kou et al., 2019 ; Yao et al., 2019 , 2020 ; Zhao et al., 2020 ). Recent studies have indicated that similar EPR effect also occurred in the inflammatory lesion, that analogous nanoparticles within certain size range could accumulate in the inflamed site through the effect of extravasation across leaky vasculature and subsequent inflammatory cell-mediated sequestration, so-called ELVIS effect (Gong et al., 2019 ).…”
Section: Formulation Approaches For Acute Pancreatitismentioning
confidence: 99%
See 1 more Smart Citation